AMEERA-5: a randomized, double-blind phase 3 study of amcenestrant plus palbociclib letrozole plus palbociclib for previously untreated ER+/HER2– advanced breast cancer - Aditya Bardia; Javier Cortes; Sara A. Hurvitz; Suzette Delaloge; Hiroji Iwata; Zhi-Ming Shao; Dheepak Kanagavel; Patrick Cohen; Qianying Liu; Sylvaine Cartot-Cotton; Vasiliki Pelekanou; Joyce O’Shaughnessy (Therapeutic Advances in Medical Oncology, 2022)
Background: For estrogen receptor–positive (ER+)/human epidermal growth factor receptor 2–negative (HER2–) advanced breast cancer (ABC), the current standard first-line treatment includes an aromatase inhibitor in combination with a cyclin-dependent kinase 4/6 inhibitor. When resistance occurs, often related to the occurrence of ESR1 mutations, selective estrogen receptor modulators or degraders (SERDs) may be used, alone or in combination regimens. Amcenestrant (SAR439859), an optimized oral SERD, has shown clinical antitumor activity in combination with palbociclib in patients with ER+/HER2– ABC and, as monotherapy, in patients with and without ESR1 mutations. Here, we describe the study design of AMEERA-5, an ongoing, prospective, phase 3, randomized, double-blind, multinational study comparing the efficacy and safety of amcenestrant plus palbociclib versus letrozole plus palbociclib in patients with advanced (locoregional recurrent or metastatic) ER+/HER2– breast cancer. Methods: Patients are pre-/postmenopausal women and men with no prior systemic therapy for ABC. The planned enrollment is 1066 patients. Patients are randomized 1:1 to either amcenestrant 200 mg plus palbociclib 125 mg or letrozole 2.5 mg plus palbociclib 125 mg. Amcenestrant, letrozole, and their matching placebos are taken once daily continuously; palbociclib is taken once daily for 21 days, followed by 7 days off-treatment for a 28-day cycle. Treatment continues until disease progression, unacceptable toxicity, or decision to stop treatment. Pre-/perimenopausal women and men receive goserelin subcutaneously. Randomization is stratified by de novo metastatic disease, menopausal status, and visceral metastases. The primary endpoint is progression-free survival. The key secondary endpoint is overall survival; others are safety, pharmacokinetics, and quality of life. Conclusions: AMEERA-5 is evaluating the efficacy and safety of amcenestrant in combination with palbociclib as first-line therapy in pre-/postmenopausal women and men with ER+/HER2– ABC. ClinicalTrials Identifier: NCT04478266.